2022
DOI: 10.1002/anie.202211031
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional‐on‐Three‐Dimensional Metal‐Organic Frameworks for Photocatalytic H2 Production

Abstract: A MOF-on-MOF heterostructure is attractive in material science because of its potential combined effects in catalysis. However, precisely controlling the growth pattern at the metal-organic framework (MOF) nucleation stage to manipulate the metallic composition and structure dimensionality remain a challenge. Herein, we introduce a polyvinylpyrrolidone-assist kinetic-control strategy to achieve the "anti-epitaxial growth" pattern of a foreign MOF nucleus on the (111) facets of UiO-66-NH 2 octahedron seeds, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…The growth of second MOF on the surface of template MOF (MOFon-MOF growth) has been well established for the conjugation of two different MOFs or the production of unique MOFs. [26][27][28][29][30][31][32][33][34][35] Especially, a well-crystallized template MOF can induce the growth of a well-crystallized second MOF. [31][32][33][34][35] The presence of well-crystallized MOF-74 should induce not only the effective growth of D-MOF-74 but also the production of D-MOF-74 with a preserved crystallinity by providing well-ordered lattices to the reactants.…”
Section: Resultsmentioning
confidence: 99%
“…The growth of second MOF on the surface of template MOF (MOFon-MOF growth) has been well established for the conjugation of two different MOFs or the production of unique MOFs. [26][27][28][29][30][31][32][33][34][35] Especially, a well-crystallized template MOF can induce the growth of a well-crystallized second MOF. [31][32][33][34][35] The presence of well-crystallized MOF-74 should induce not only the effective growth of D-MOF-74 but also the production of D-MOF-74 with a preserved crystallinity by providing well-ordered lattices to the reactants.…”
Section: Resultsmentioning
confidence: 99%
“…One peak is at ∼1.6 Å in R space and ∼7.8 Å −1 in k space, which is ascribed to the Ir–N(O) path. 51–53 Fig. 2g shows the Ir L 3 -edge XANES spectra of Ir SA -NS-Ti 3 C 2 T x with different doping amounts of the precursor thiourea, in which the increase of white-line intensity has a nearly linear relation with the increase of the precursor thiourea, indicating the change of the average oxidation state for single atom Ir due to the EMSI interaction between single-atom Ir and the Ti 3 C 2 T x MXene support.…”
Section: Resultsmentioning
confidence: 99%
“…[119][120][121] Recently, Wang et al reported a new antiepitaxial growth pattern in constructing a "dimensionality-hybrid" 2D-on-3D MOF with ultrathin 2D coverlayer for photocatalytic H 2 generation. [122] The successful anisotropic growth of 2D MOFs at a single MOF level requires lattice matching between the host MOF and secondary guest MOF; therefore, a stable Zr-based UiO-66-NH 2 octahedron (U6N) with (111) lattice fringe of 1.20 nm was selected as the seed MOF, and a Cu-TCPP MOF with (110) lattice fringe of 1.17 nm was chosen as the secondary guest 2D MOF. The deposition of 2D Cu NS on 3D U6N may be achieved by electrostatic attraction with PVP-assisted kinetic control (Figure 13A).…”
Section: Active Sites At the Pore Space Of Zr-mofmentioning
confidence: 99%
“…C) The proposed mechanism of enhanced charge separation ability of 2D-on-3D structure compared with the 3D-on-3D structure. Reproduced with permission [122]. Copyright 2022, Wiley-VCH.…”
mentioning
confidence: 99%